Néhány választott egyéni sportág jelenlegi helyzetének és versenyképességének elemzése Magyarországon - Madarász, Tamás (International Journal of Engineering and Management Sciences, 2016)
In the past few years, our country increased importance of sports. 2010 was highlighted in 16 individual sports, which receive state subsidies for the period 2013-2020. In this research we selected the four disciplines of sports - canoeing, modern pentathlon, wrestling, judo - I examined the domestic situation and competitiveness. The sports competitiveness investigated on the basis of their role in the media occupied, according to the method of the International Olympic Committee (IOC). The IOC and the Olympic Games Organising Committee (OCOG) mediation from the proceeds distributed to sports, by way of support. I think it is important to examine the competitiveness of sports, and international jótapasztalatokat used later to propose solutions to increase viewing figures. The first stage of this research, which shows the position of sports Hungary, explore their differences and draw parallels between the similarities.